2017
DOI: 10.17051/ilkonline.2017.330232
|View full text |Cite
|
Sign up to set email alerts
|

Teknolojik Pedagojik Alan Bilgisi (TPAB) Kavramının Yakından İncelenmesi: İlköğretim Fen Bilgisi Öğretmen Adaylarının TPAB’ ının Modellemesi

Abstract: ABSTRACT. TPACK (Technological pedagogical content knowledge) is a useful framework for integrating technology into teaching for meaningful understanding. Since its introduction by Mishra and Kohler in 2006, there is no consensus in the results of the studies examining structure of TPACK. Recently, some studies have focused on TPACK self-efficacy (TPACK-SE) beliefs. We aimed to validate factor structure of TPACK-SE and reveal the relations among the components. A structural equation model (SEM) formed in light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
(51 reference statements)
1
2
0
1
Order By: Relevance
“…They tried to mix and match any teaching strategies with the technology they would use and vice versa to meet the desired teaching plan. However, Günbatar et al, (2017) support the fact found in this study that PK might have more relationship to TPK's increasing percentage as PK's percentage raising margin was higher (40%) than TK's percentage raising margin (20%). This finding was assumed to be correlated with PSTs' habit to think about the teaching strategy or method earlier before choosing technology to use for support, like what was said by Participant 5.…”
Section: Discussionsupporting
confidence: 89%
“…They tried to mix and match any teaching strategies with the technology they would use and vice versa to meet the desired teaching plan. However, Günbatar et al, (2017) support the fact found in this study that PK might have more relationship to TPK's increasing percentage as PK's percentage raising margin was higher (40%) than TK's percentage raising margin (20%). This finding was assumed to be correlated with PSTs' habit to think about the teaching strategy or method earlier before choosing technology to use for support, like what was said by Participant 5.…”
Section: Discussionsupporting
confidence: 89%
“…Numerous scales have been developed to measure TPACK self-efficacy of prospective teachers (Aydın-Gunbatar, Boz, & Yerdelen-Damar, 2017;Chai, Koh, Tsai, & Tan, 2011;Kabakci Yurdakul, Odabasi, Kilicer, Coklar, Birinci, & Kurt, 2012). Prospective teachers' TPACK self-efficacy measurement tools are about their availability to integrate technology in education.…”
Section: Technological Pedagogical Content Knowledge Modelmentioning
confidence: 99%
“…The knowledge domains in the TPACK model have a significant and positive correlation with self-efficacy beliefs about technology integration (Abbit, 2011b;Lee & Tsai, 2010). Therefore, it is important to reveal teachers' self-efficacy beliefs about TPACK (Lee & Tsai, 2010;Aydın-Günbatar, Boz, & Yerdelen-Damar, 2017).…”
Section: Figure 1 Components Of Tpack Structurementioning
confidence: 99%